2021
DOI: 10.1111/jgs.17113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of new Medicare enrollment on health, healthcare utilization, and cost: A scoping review

Abstract: Background More than three million Americans turn 65 each year and newly enroll in Medicare, making this one of the most common insurance transitions. Non‐Medicare insurance transitions are associated with changes in health, healthcare utilization and costs. In addition, older Americans have higher morbidity, mortality, healthcare utilization, and healthcare costs than the general population. However, the effect of new Medicare enrollment on these outcomes is unclear. Design We conducted a scoping review to ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Despite having relatively lower age-adjusted rates of cytology/HPV testing, Hispanic and non-Hispanic Black populations have maintained higher overall age-adjusted rates of colposcopy and cervical procedures. This could represent increased use of health care services after becoming Medicare eligible and an associated detection of previously undetected abnormalities, especially as older Hispanic and non-Hispanic Black populations are much more likely to be overdue for cervical cancer screening . Future studies investigating these populations on a more granular level could provide insight into the cervical cancer incidence disparities seen in older individuals by racial and ethnic groups …”
Section: Discussionmentioning
confidence: 99%
“…Despite having relatively lower age-adjusted rates of cytology/HPV testing, Hispanic and non-Hispanic Black populations have maintained higher overall age-adjusted rates of colposcopy and cervical procedures. This could represent increased use of health care services after becoming Medicare eligible and an associated detection of previously undetected abnormalities, especially as older Hispanic and non-Hispanic Black populations are much more likely to be overdue for cervical cancer screening . Future studies investigating these populations on a more granular level could provide insight into the cervical cancer incidence disparities seen in older individuals by racial and ethnic groups …”
Section: Discussionmentioning
confidence: 99%
“…Medicare eligibility has previously been associated with increased health care utilization in terms of hospitalizations, office visits, and age-appropriate preventive care. 2,6,[19][20][21] Increased preventive care with Medicare eligibility may play a role in driving the observed increase in bladder and kidney cancer diagnosis and survival due to the incidental detection of microhematuria on urinalysis, a common component of routine labs. Medicare-eligible individuals have previously been found to undergo more frequent screening for colorectal, breast, and prostate cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Americans with little to no health care coverage before enrolling in Medicare have previously been demonstrated to increase their utilization of health care services, including catching up with age-appropriate screenings that had been missed in the years prior. [4][5][6][7][8] Many of these screenings are aimed at detecting cancer. For the underinsured, routine screening or evaluation of cancer symptoms may have been delayed until the onset of Medicare eligibility.…”
mentioning
confidence: 99%
“…We used data from 2011 as a 1-year washout period to exclude all temporary ED users identified in the baseline year who had an ED visit in 2011. For each state, only ED visits by in-state residents aged 18–59 in 2012 were included to avoid new enrolment to Medicare (the federal health insurance program for those who are 65 or older) at the age of 65 later in the study period, as having Medicare has been shown to affect healthcare utilisation 18 21. Individuals who died in the baseline year were also excluded.…”
Section: Methodsmentioning
confidence: 99%